Surface Modification of Ti-6Al-4V Alloy By Anodization Technique at Low Potential to Produce Oxide Layer - Franciska Pramuji Lestari; Yeni Rian Sari; Fendy Rokhmanto; Talitha Asmaria; Andika Widya Pramono (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
Due to their excellent biocompatibility, titanium alloys are tremendously as implants used, since relatively low modulus, corrosion resistance, and good fatigue strength. The biocompatibility, comes from the formation of natural Titanium dioxide (TiO2) layer. Therefore, TiO2 layer growth surface alteration is frequently applied to improve biological, chemical , and mechanical properties. TiO2 nanostructures are obtained under self-organization conditions by electrochemical anodization of Ti-6Al-4V. Parameters of anodization such as anodization time, voltage and addition of thiourea were evaluated in the composition of the H3PO4+NH4F solution. The morphology and elements of the Ti alloys surface were analyzed by Scanning Electron Microscopy (SEM) and Energy-Dispersive Spectroscopy (EDS), whereas potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) were used to evaluate the TiO2 layer in corrosion resistance. The results showed that the anodized Ti-6Al-4V alloy E-corr imcreased as the anodization voltage increased. Titanium alloy anodized using 12 V during 2 hours with H3PO4 + NH4F without thiourea solution had the thickest of oxide layer and highest corrosion resistance. Higher applied voltages have been shown to increase the deposition rate and coating thickness. Addition of thiourea has a definite effect on the inhibition of oxide layer of titanium. In order to produce the optimum titanium surface, the required applied anodization voltage and addition of volume thiourea is necessary.